Buspirone Counteracts MK-801-Induced Schizophrenia-Like Phenotypes through Dopamine D3 Receptor Blockade - Torrisi, Sebastiano Alfio; Salomone, Salvatore; Geraci, Federica; Caraci, Filippo; Bucolo, Claudio; Drago, Filippo; Leggio, Gian Marco (Frontiers in Pharmacology, 2017)
Several efforts have been made to develop effective antipsychotic drugs. Currently available antipsychotics are effective on positive symptoms, less on negative symptoms, but not on cognitive impairment, a clinically-relevant dimension of schizophrenia. Drug repurposing offers great advantages over the long-lasting, risky and expensive, de novo drug discovery strategy. To our knowledge, the possible antipsychotic properties of buspirone, an azapirone anxiolytic drug marketed in 1986 as serotonin 5-HT1A receptor (5-HT1AR) partial agonist, have not been extensively investigated despite its intriguing pharmacodynamic profile, which includes dopamine D3 (D3R) and D4 receptor (D4R) antagonist activity. Multiple lines of evidence point to D3R as a valid therapeutic target for the treatment of several neuropsychiatric disorders including schizophrenia. In the present study, we tested the hypothesis that buspirone, behaving as dopamine D3R antagonist, may have antipsychotic-like activity. Effects of acute administration of buspirone was assessed on a wide-range of schizophrenia-relevant abnormalities induced by a single administration of the non-competitive NMDAR antagonist MK-801, in both wild-type mice (WT) and D3R-null mutant mice (D3R-/-). Buspirone (3 mg·kg-1, i.p.) was devoid of cataleptogenic activity in itself, but resulted effective in counteracting disruption of prepulse inhibition (PPI), hyperlocomotion and deficit of temporal order recognition memory (TOR) induced by MK-801 (0.1 mg·kg-1, i.p.) in WT mice. Conversely, in D3R-/- mice, buspirone was ineffective in preventing MK-801-induced TOR deficit and it was only partially effective in blocking MK-801-stimulated hyperlocomotion. Taken together, these results indicate, for the first time, that buspirone, might be a potential therapeutic medication for the treatment of schizophrenia. In particular, buspirone, through its D3R antagonist activity, may be a useful tool for improving the treatment of cognitive deficits in schizophrenia that still represents an unmet need of this disease.